The Five Leadership Style in Time of Pandemic Covid-19 throughout Industrial Revolution 4.0 as compared to Humane Leadership - Leo Hutagalung; AGUS PURWANTO; Agustian Budi Prasetya (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2020)
Covid-19 has create a confusion among organizations that leaders without any preparation must focus their attention to the kind of leadership which suitable to the pandemic condition. Leadership must have competence to handle a new problem so that leadership must be explicitly mastered. Leaders must master the lead methods, especially influencing subordinates to work optimally even the conditions are affected by unpredicted circumstances. Even leaders must be able to prepare backup steps as contingencies on operational standards and procedures within the pandemic environment. The article is proposing 5-type of leadership that is comprehensive and exploring the necessary attentions which improve the quality of leadership throughout pandemic covd-19 as well as entering the industrial revolution 4.0. This combination of leaderships would be compared to the humane leadership by all means as resume the application.